Bioprospecting hydroxylated chalcones in in vitro model of ischemia-reoxygenation and probing NOX4 interactions via molecular docking - Ali, Arif (2024)
Ischemia reperfusion injury (I/R) is a prevalent cause of acute kidney injury (AKI) in various clinical conditions including kidney transplant, cardiac surgeries, and nephrectomy, significantly contributing to high rate of mortality and morbidity around the globe. The aim of this study was to evaluate the protective role 2'-hydroxychalcones in treatment of I/R induced AKI by targeting main pathological pathways including generation of ROS, early apoptosis, necrosis, antioxidant system and NOX4 interactions. Chalcones derivatives are studied widely due to their simple structure and numerous biological activities such as antioxidant, anti-inflammatory, anti-microbial, anticancer, antidiabetic, psychoactive and neuroprotective actions. Therefore, considering strong antioxidant action along with other pharmacological roles of chalcone derivatives, six 2'-hydroxychalcones were synthesized through a Claisen- Schmidt condensation reaction initiated with 2-hydroxyacetophenone. These chalcone derivatives were then analyzed for their protective role in I/R induced AKI in HK-2 cells. Primarily, cell viability was analyzed via MTT assay, followed by flow cytometry for apoptosis, necrosis, ROS generation and mitochondrial transmembrane potential evaluation. The effect of chalcone molecules on oxidation- reduction balance was evaluated by analyzing its effect on TBARS, GSH and SOD. The I/R induced morphological changes were assessed via scanning electron microscope (SEM). And to identify an interaction with NOX4, molecular docking was performed. The results of the study showed, that among six 2'-hydroxychalcones, (E)-1-(2-hydroxyphenyl)-3-(4-methoxyphenyl)-prop-2-en-1-one (chalcone A4) has significantly increased the HK-2 cells viability compared to I/R group. Chalcone A4 has reduced the cell death events by reducing generation of cytoplasmic ROS and mitochondrial transmembrane potential. Similarly, chalcone A4 treatment has increased GSH and SOD activity while reduced the level of TBARS, signaling towards its strong antioxidant action. The SEM images showed chalcone A4 protective action on HK-2 cells where it has reversed the I/R induced morphological alterations including apoptosis blebbing’s and cytoplasm fragmentation. Moreover, in silico study of chalcone A4 demonstrated potential interactions with NADPH oxidase 4 enzyme, hence providing further evidences of their protective role against I/R induced AKI. These results showed that Chalcone A4 possess potential protective action against I/R induced cellular damage possibly due to its strong antioxidant potential and interaction with NOX4 subunit of NADPH oxidase.